Gray Wolf Diet Composition in California’s Human-Dominated Landscape - Tina L. Saitone; Kenneth W. Tate; Benjamin J. Sacks (PLoS ONE, 2026)
Gray wolves have successfully recolonized much of their historical range on multiple continents, now occupying landscapes substantially altered during their absence. Wolf ecological function in human-modified landscapes remains poorly understood, fueling conflict concerns among rural stakeholders and conservation advocates over predation on economically valuable livestock and wildlife. Dietary studies can facilitate prediction of ecological impacts and help avoid outcomes that undermine human-wolf coexistence and conservation objectives. This study addresses a critical gap in dietary research of a recolonizing population of wolves in California, USA, representing the first investigation employing genetic identification of species and individuals combined with DNA metabarcoding for diet determination in scat samples. Our findings indicate that cattle dominated wolf diet, occurring in 72% of samples during the study period, compared to mule deer, which occurred in 45% of samples and small mammals that appeared in 51% of samples. Dietary biomass estimates corroborated cattle as the principal dietary component accounting for an average of 55%, while mule deer and small mammals each contributed considerably smaller proportions, 12% and 15%, respectively. These results revealed that wolves in California’s human-modified landscape primarily satisfy their caloric requirements through livestock consumption, underscoring the considerable challenges posed by coexistence of wolves and humans within the state.